PENGEMBANGAN MODEL EVALUASI KINERJA GURU BERSERTIFIKASI DI PURWOKERTO BANYUMAS - Nurfuadi Nurfuadi; Supriyanto Supriyanto; Maridi Maridi (IAIN Purwokerto, 2017)
Abstract: Teachers as a part of professional educators are having the main task of educating, teaching, guiding, directing, training, assessing, and evaluating learners in early childhood education on formal education, primary education and secondary education. In performing their duties, teachers apply skills, skills that suitable with the quality standards or specific norms they obtain through professional education. The target of this research is the teachers who have passed the certification and have received professional allowance from 2008 in Banyumas District Education Office. Data on these teachers is based on the data sourced from Teachers Certification Teams of Banyumas District Education Office. The total amount of teachers who have passed the certification and received professional allowance in Education Department of Banyumas Regency as many as 6,884 people. Keywords: Model Development, Performance Evaluation, Teacher Certified